Ciri Kepercayaan Zaman Prasejarah dan Animisme : Penilaian Semula Buku Teks Sejarah Mengikut Perspektif Islam: Features of Beliefs and Animism in Prehistoric Period: Re-Evaluation of History Textbooks According to Islamic Perspective - Mohd Nasir, Mohd Khairulnazrin; Ahmad, Khadher (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2023)
Various theories on the characteristics of human beliefs existed in prehistoric period. Among the well-known theories is the theory of animism. One of the prominent scholars in animism is Edward Burnett Tylor, who is also known as the father of anthropology. Animism is a belief that everything in this world possesses soul and spirit. This theory is incorporated in the history books and one of them is the Form One History textbook, published by the Ministry of Education Malaysia. This article purports to provide an assessment and re-elaboration of the characteristics of human beliefs in prehistoric period based on Islamic perspectives. The method used was the library research with the application of descriptive and critical elements. The finding showed that the characteristic of human belief during prehistoric period was tauhid and not animism. Hence, the information in the textbook should be revised, by implementing the Islamic historical data.